Using PES to Implement REDD - Pagiola, Stefano (World Bank, Washington, DC, 2014)
Payments for Environmental Services (PES) are one of the instruments that countries might use to try to reduce deforestation, and hence receive payments for Reduced Emissions from Deforestation and forest Degradation (REDD). This paper discusses four aspects related to the use of PES as an instrument to implement an avoided deforestation program, based on a review of PES experiences in Latin America. First, the paper discusses the applicability of PES in the context of REDD. PES is only one of the instruments that can be used to reduce deforestation. Some types of deforestation problems may not be amenable to the use of PES, while others might be better addressed with other instruments. Second, the paper examines the evidence on the effectiveness of PES as a tool to reduce deforestation. Although it seems intuitive to think that paying for forest conservation would reduce deforestation, the available evidence from existing PES programs is mixed. Third, the paper discusses several welfare considerations arising from the possible use of PES as a tool to reduce deforestation. That REDD be implemented in ways that do not harm the welfare of forest-dependent peoples has been an important part of the debate.